Entrepreneurship over the Business Cycle in the United States: A Decomposition - Frank M. Fossen (Institute of Labor Economics (IZA), 2019)
Entry rates into self-employment increase during recessions and decrease during economic upswings. I show that this is mostly explained by the higher unemployment rate during a recession, together with the fact that at all times, unemployed persons have a relatively high propensity to become entrepreneurs out of necessity because they do not find paid employment. I use econometric decomposition techniques to quantify these effects based on the monthly matched US Current Population Survey before, during and after the Great Recession. I also document that this counter-cyclical pattern of entrepreneurial entry strongly applies to unincorporated entrepreneurship, but only weakly to incorporated entrepreneurship. This highlights the association of unincorporated and incorporated entrepreneurship with necessity and opportunity entrepreneurship, respectively. The results are useful for policy-makers and practitioners to understand, forecast and act on the different types of entrepreneurial activities that are to be expected over the business cycle.
Keywords: L26; J22; J23; M13; 330; entrepreneurship; business cycle; Great Recession; unemployment; opportunity; necessity; decomposition